Strengthening communities’ disaster resilience during COVID-19 time: A case of Muhammadiyah in Indonesia - Umi Qodarsasi; Riza Nuzulul Huda; Umaroh Anisa Zuma (SIMULACRA: JURNAL SOSIOLOGI, 2021)
Since the early of March 2020, COVID-19 pandemic which broke out in Indonesia, had a significant impact on various aspects of life. The pandemic not only has pushed the government to take a strategic decision but also has forced the communities to accommodate this condition immediately. Muhammadiyah is one of Indonesia’s largest religious organizations has played its role to overcome COVID-19 pandemic alongside with the government. This study aims to determine the contribution of Muhammadiyah to tackle the pandemic by strengthening the disaster resilience community. The study uses a qualitative approach and a descriptive method. The primary data were obtained by in-depth interviews with Muhammadiyah organization leaders and several working teams handling the pandemic. Literature study was conducted as the secondary data. To tackle the pandemic by strengthening communities’ disaster resilience, Muhammadiyah carried out several programs, including (1) strengthening da’wah networks massively to enhance the community awareness about COVID-19 pandemic, (2) establishing several working teams handling the pandemic to enhance disaster resilience communities, including Muhammadiyah COVID-19 Command Center (MCCC), Muhammadiyah Disaster Management Center (MDMC), and philanthropic body of Muhammadiyah (LazisMu), and (3) Muhammadiyah engagement with stakeholders and development agency, such as the collaboration with the Ministry of Health, BNPB, DFAT and USAID to COVID-19 preventive and curative action.